Public Policy and Digital Participation: Their Impact on Government Transparency and Accountability - Asrijal, Andi; Indrawati, Raden Ajeng; Zulkifli, Zulkifli (Socious Journal, 2025)
This study aims to analyze the relationship between public policy and digital participation and its impact on government transparency and accountability. Using a qualitative approach with a literature review method, this study examines various academic sources and international agency reports to identify conceptual patterns in digital governance practices. The analysis shows that the digitalization of public policy not only accelerates administrative processes but also reforms the governance paradigm towards structural transparency based on open data. Digital participation acts as a democratic mechanism that strengthens social accountability through citizen involvement in direct oversight of public policy. However, challenges such as the digital divide, data security, and information ethics remain obstacles to realizing inclusive digital governance. This study emphasizes that the success of digital public policy is determined by the synergy between technological innovation, public digital literacy, and the government's ethical commitment to openness. Therefore, digital transformation must be viewed not merely as a technocratic agenda, but as an instrument of socio-political reform that strengthens the legitimacy and public trust in government in the global information era.